2021
DOI: 10.3390/ijerph182111056
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dietary Habits and Type 2 Diabetes Mellitus in Yangon, Myanmar: A Case–Control Study

Abstract: In Myanmar, the escalating prevalence of type 2 diabetes mellitus (T2DM) and impaired glucose tolerance among adults was recently reported, with the highest prevalence in the Yangon Region. The aim of the present study was to identify the risk factors in dietary habits and their relationship with T2DM in urban Myanmar residents. We conducted a case–control study recruiting 300 individuals aged 25–74 years living in the Yangon Region, consisting of 150 newly diagnosed cases attending a diabetes clinic, and 150 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…This result is supported by the odds ratio, which showed that dietary diversity was a protective factor (OR= 0.1 [0.07-0.280]) against type 2 diabetes. Other authors have found similar results [13,28]. These researchers showed that insufficient dietary quality was a risk factor for type 2 diabetes, even though they used other types of dietary diversity scores.…”
Section: Discussionmentioning
confidence: 56%
“…This result is supported by the odds ratio, which showed that dietary diversity was a protective factor (OR= 0.1 [0.07-0.280]) against type 2 diabetes. Other authors have found similar results [13,28]. These researchers showed that insufficient dietary quality was a risk factor for type 2 diabetes, even though they used other types of dietary diversity scores.…”
Section: Discussionmentioning
confidence: 56%
“…According to a study result examining the association between dietary habits and T2DM conducted by our research team in Myanmar, it was observed that the consumption of salty seasonings with daily meals is significantly linked to a higher prevalence of T2DM. 45 Rasouli et al confirmed the notable association between high sodium intake and the elevated risk of T2DM through the findings of their population-based study conducted in Sweden. 46 …”
Section: Discussionmentioning
confidence: 86%
“…Similarly, Matti A. Vuori et al has emphasized that high sodium intake is associated with an increased incidence of cardiovascular disease and diabetes (29). Furthermore, sodium intake adds to the risk of 2 diabetes was widely reported in Asia, such as China, Korea and Japan where pickles and sauces are popular (30)(31)(32). For the first time, our examination of a nationally representative non-institutional members in the United States corroborates previous research indicating a positive correlation between higher sodium intake and an increased risk of diabetes.…”
Section: Discussionmentioning
confidence: 98%